2013
DOI: 10.1016/j.jhealeco.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Health expenditure growth: Looking beyond the average through decomposition of the full distribution

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 42 publications
3
26
1
1
Order By: Relevance
“…As a result, the Netherlands is now the country with the highest level of spending on health care in the world after the United States (OECD, 2015). Much of the increase in spending since 2001 was the result of a greater propensity to use hospital care, as well as the introduction of new technologies (De Meijer et al 2013). …”
Section: Trends In Aggregate Health Expenditurementioning
confidence: 99%
“…As a result, the Netherlands is now the country with the highest level of spending on health care in the world after the United States (OECD, 2015). Much of the increase in spending since 2001 was the result of a greater propensity to use hospital care, as well as the introduction of new technologies (De Meijer et al 2013). …”
Section: Trends In Aggregate Health Expenditurementioning
confidence: 99%
“…The difference is explained by the sum of a composition effect produced by the differences in the characteristics of the two populations and a structure effect generated by the differences in the population-specific distributions. The latter is also called a conditional distribution effect by De Meijer et al (2013).…”
Section: Simulating a Counterfactual Distributionmentioning
confidence: 99%
“…A continuum of indicator variables needs to be generated and then regression models are used to construct the conditional distribution functions for each value. Given the computational demand of this approach and lack of variation in the indicator variables at low and high costs, de Meijer et al () use linear probability models in place of logit regressions. We also adopt this approach in our comparison, because preliminary work showed that, where it was possible to estimate both logit and linear probability models, there was little difference between the methods.…”
Section: Empirical Modelsmentioning
confidence: 99%
“…More recently, Chernozhukov et al () propose that a continuum of logits should be estimated (one for each unique value of the outcome variable) to allow for an even greater range of estimates for the effect of a covariate. In an application to Dutch health expenditures, de Meijer et al () use the Chernozhukov et al () method to decompose changes in the distribution of health expenditures between two periods. The authors find that the effect of covariates varies across the distribution of health expenditures, which would have been missed if analysis had focused solely on the mean.…”
Section: Introductionmentioning
confidence: 99%